2021
DOI: 10.1038/s41598-021-93951-w
|View full text |Cite
|
Sign up to set email alerts
|

Engineered mucoperiosteal scaffold for cleft palate regeneration towards the non-immunogenic transplantation

Abstract: Cleft lip and palate (CL/P) is the most prevalent craniofacial birth defect in humans. None of the surgical procedures currently used for CL/P repair lead to definitive correction of hard palate bone interruption. Advances in tissue engineering and regenerative medicine aim to develop new strategies to restore palatal bone interruption by using tissue or organ-decellularized bioscaffolds seeded with host cells. Aim of this study was to set up a new natural scaffold deriving from a decellularized porcine mucope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The results showed that the collagen mesh was preserved, causing an increase in the osteoinductive potential of the mesenchymal precursor cells. This scaffold has a potential impact on palatal bone regeneration, which could lead to future clinical applications in humans [ 90 ].…”
Section: Biomaterials Applied In the Regeneration Of The Cleft Palatementioning
confidence: 99%
“…The results showed that the collagen mesh was preserved, causing an increase in the osteoinductive potential of the mesenchymal precursor cells. This scaffold has a potential impact on palatal bone regeneration, which could lead to future clinical applications in humans [ 90 ].…”
Section: Biomaterials Applied In the Regeneration Of The Cleft Palatementioning
confidence: 99%
“…SCs seem to present as a favorable option for bone regeneration in the oro-maxillofacial region with potential use in alveolar defect regeneration and reducing defect sizes by new bone formation [ 23 , 25 , 26 ], with less postoperative morbidity compared to autogenous bone grafting [ 27 ]. It also seems that teeth in the defect area tend to erupt in their proper position [ 28 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…Clinicians and researchers have been working together to search for applicable stem cell-based tissue engineering to overcome these challenges [14,15,51]. Unlike alveolar cleft, stem cell-based tissue engineering technology for cleft palate is still in process for future clinical human application [52]. In addition, the application of new technologies for oral cleft treatments is often hampered by limited healthcare settings where many patients are left untreated until they reach adult age [11].…”
Section: Discussionmentioning
confidence: 99%